LEGAL PROTECTION OF OUTSOURCED WORKERS UNDER LAW NO. 6/2023: A PT. SSBI SIDOARJO CASE - Sofianti, Elsa; Razak, Muhammad Abdul (YURIS: Journal of Court and Justice, 2025)
Many companies in Indonesia have now implemented the outsourcing system with the aim of reducing labor costs. Regarding the implementation of this outsourcing system, it is actually regulated in the Job Creation Law Number 6 of 2023. With the ratification of the job creation law, it is hoped that companies can fulfill their obligations by providing legal protection to workers according to their rights. The aim of this research is to find out an exact picture of the legal protection of outsourced workers relating to fixed-term work agreements in accordance with the Job Creation Law Number 6 of 2023, especially Article 66 which is currently in effect. This research also aims to determine the influence of the Job Creation Law Number 6 of 2023 on outsourcing workers in the case study PT. SSBI Sidoarjo. This research uses empirical research by describing the main problems that exist in society based on the results of case studies in the field and secondary data as support.  Based on the results of this research, the obligations of PT. SSBI Sidoarjo to provide legal protection to its outsourced workers, especially regarding Article 66 concerning employment relations related to certain term work agreements, is in accordance with the Job Creation Law Number 6 of 2023 which is currently in effect, the rights obtained by outsourced workers at PT. SSBI Sidoarjo is related to legal protection, namely: the right to wages, the right to work safety, the right to health, and the right to leave, so this has impact on the welfare of outsourced workers at PT. SSBI Sidoarjo.